2015
DOI: 10.1586/14737167.2015.1021336
|View full text |Cite
|
Sign up to set email alerts
|

Do different decision-analytic modeling approaches produce different results? A systematic review of cross-validation studies

Abstract: When choosing a modeling approach for health economic evaluation, certain criteria are often considered (e.g., population resolution, interactivity, time advancement mechanism, resource constraints). However, whether these criteria and their associated modeling approach impacts results remain poorly understood. A systematic review was conducted to identify cross-validation studies (i.e., modeling a problem using different approaches with the same body of evidence) to offer insight on this topic. With respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…A recent systematic review was published focused on cross-validation work in health economic models, evaluating the impact of structural features on the choice of the modelling approach [20]. Population resolution was found to have minimal impact empirically as both aggregate- and individual-level models generated nearly identical results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review was published focused on cross-validation work in health economic models, evaluating the impact of structural features on the choice of the modelling approach [20]. Population resolution was found to have minimal impact empirically as both aggregate- and individual-level models generated nearly identical results.…”
Section: Discussionmentioning
confidence: 99%
“…individual-level models required fewer simplifying assumptions, thus increasing its face validity but at the expense of being more time- and data-intensive; and vice versa). In terms of the criterion of interactivity, infectious-disease models have consistently showed that, depending on the assumptions regarding the probability of disease exposure, dynamic and static models will produce dissimilar results and lead to opposing policy recommendations [20]. Further research in this area is still required as it may provide the evidence that is necessary to better guide the development of evidence-based decision frameworks.…”
Section: Discussionmentioning
confidence: 99%
“…Beside the suitability of the modelling framework, the way these methods are implemented in practice (i.e. what structural assumptions are made) can affect the validity of costeffectiveness findings 15 . Comparably to how the National Institute of Health and Care Excellence (NICE)NICE evaluates models included as part of manufacturers submissions 33 , previews attempts to critique the plausibility of key structural assumptions of the models have been made in other public health evaluation settings 10,16 .…”
Section: Modelling Framework Available To Analystsmentioning
confidence: 99%